Implementing recommended breastfeeding practices in healthcare facilities in India during the COVID-19 pandemic: a scoping review of health system bottlenecks and potential solutions - Dudeja, Nonita; Sharma, Divita; Maria, Arti; Pawar, Priyanka; Mukherjee, Ritika; Nargotra, Shikha; Mohapatra, Archisman (Frontiers in Nutrition, 2023)
Background Breastfeeding practices in institutional settings got disrupted during the COVID-19 pandemic. We reviewed the challenges faced and the “work-around” solutions identified for implementing recommended breastfeeding practices in institutionalized mother-newborn dyads in resource constrained settings during the pandemic with the aim to identify learnings that could be potentially adapted to the Indian and relatable contexts, for building resilient health systems. Methods We conducted a scoping review of literature using the PRISMA ScR Extension guidelines. We searched the Medline via PubMed and Web of Science databases for literature published between 1st December 2019 and 15th April 2022. We included original research, reviews, and policy recommendations published in English language and on India while others were excluded. Further, we searched for relevant gray literature on Google (free word search), websites of government and major professional bodies in India. Three reviewers independently conducted screening and data extraction and the results were displayed in tabular form. Challenges and potential solutions for breastfeeding were identified and were categorized under one or more suitable headings based on the WHO building blocks for health systems. Results We extracted data from 28 papers that were deemed eligible. Challenges were identified across all the six building blocks. Lack of standard guidelines for crisis management, separation of the newborn from the mother immediately after birth, inadequate logistics and resources for infection prevention and control, limited health workforce, extensive use of formula and alternative foods, inconsistent quality of care and breastfeeding support, poor awareness among beneficiaries about breastfeeding practices (and especially, about its safety during the pandemic) were some of the challenges identified. The solutions primarily focused on the development of standard guidelines and operating procedures, restricted use of formula, use of telemedicine services for counseling and awareness and improving resource availability for risk mitigation through strategic mobilization. Conclusion The COVID-19 pandemic has provided rich learning opportunities for health system strengthening in India. Countries must strengthen learning mechanisms to identify and adapt best practices from within their health systems and from other relatable settings.